The Relationship of Smoking Status on the Severity of Psoriasis Patients in Dermatology and Venereology Outpatient Clinic of Dustira Hospital 2024 - Lina Damayanti; Ali Taufan; Rina Munirah; Razqia Dhianrha Naziffa (Jurnal EduHealth, 2025)
Psoriasis is a chronic inflammatory skin disease characterized by erythematous lesions, epidermal hyperplasia, and firmly demarcated white, silver-like scales. This disease has varying degrees of severity and can be influenced by various factors, one of which is smoking status. This study aims to analyze the relationship between smoking status on the severity of psoriasis patients in the Dermatology and Venereology outpatient clinic of Dustira Hospital in 2024. This type of research is analytic observational with a cross-sectional research design. Observations were made of smoking status variables and psoriasis severity at one specific time. Data were collected through interviews and examination of patient severity based on Body Surface Area (BSA) scores. Data analysis was performed with the chi-square statistical test to determine the relationship between variables. The results showed a significant relationship between smoking status and psoriasis severity, with a p-value of 0.014 (p-value = 0.014 < 0.05). The conclusion of this study is that smoking status has a significant relationship with psoriasis severity. These results underscore the importance of efforts to reduce smoking status in order to manage psoriasis severity in patients.